Forecasting Simcard Demand Using Linear Regression Method - Sitompul, Monica; Hasan, Mhd Arief; Devega, Mariza (UIR PRESS, 2023)
The purpose of this research is to get a prediction of how package card growth will be based on sales data from SINAR E-XIX CELL. The method used for this forecasting is linear regression, based on the number of card packs sold which is the causal variable. The accuracy of predictions is carried out using Python based on the results of research conducted with data on simcard sales over a period of two years, it was found that in the following year the number of growth in demand for sim cards in the coming year has decreased, but there is one card that has experienced an increase in the number of growth in the following year. which will come. Forecasting using Linear Regression can be said to be classified as very well based on using python. After doing the forecasting it can be concluded that in the next few years the demand for cards will be less.